Prevalence and associated factors of diabetic foot at risk among type 2 diabetes mellitus patients attending primary health clinics in Kuantan - Nurul Husna binti Azmi
Introduction: Foot complications are considered to be a serious consequence of diabetes mellitus, posing a major medical and economic threat. The diabetic foot at risk is the diabetic foot which is at risk of ulceration, hence the importance of identifying the foot at this stage. This study aims to assess the prevalence of diabetic foot at risk and its associated factors among the type 2 diabetes mellitus patients' attending primary health clinics in Kuantan. Methods : This was a cross sectional study conduc ted at four primary health clinics in Kuantan involving 450 study participants who were selected by using universal sampling method. Level of awareness and practice toward diabetic foot care was assessed using validated self administered questionnaire. Foo t examination carried out and foot at risk was classified based on Kings' Classification. Multiple logistic regressions were performed to identify the risk factors for diabetic foot at risk. Results : The prevalence of diabetic foot at risk was 31.3% (95% CI: 0.27, 0.36) according to Kings Classification (stage 2). Mean age of respondents involved was 56.36 (SD±10.9) years. Multivariate logistic regression analysis identified age (OR 1.04, 95% CI: 1.01 1.06), smoker (OR 4. 11, 95% CI: 1.96 8.63) and duration of diabetes more than 10 years (OR1.77, 95 CI : 1.05 2.98) were risk factors for diabetic foot at risk. Respondents with good practice score (OR 0.87, CI: 0 .77 0.98 ) have lesser risk of developing diabetic foot at risk. However, level of awareness, race, gender, education level and diabetic control did not show any significant association with diabetic foot at risk. Conclusion : Patients who are older, smokers and/or have chronic diabetes are predicted to be at higher risk to develop the diabetic foot at risk. Therefore, these are the group of patients that need to be targeted for early detection and intervention to prevent serious complications. This study also showed that patients with better foot care practice has lesser risk, hence a sustainable patient education and compliance towards practice of foot care at primary care level should be emphasized more.